Barriers to early diagnosis of symptomatic breast cancer: a qualitative study of Black African, Black Caribbean and White British women living in the UK. Issue 3 (13th March 2015) - Jones, Claire E L; Maben, Jill; Lucas, Grace; Davies, Elizabeth A; Jack, Ruth H; Ream, Emma
Abstract : Objectives: Understanding barriers to early diagnosis of symptomatic breast cancer among Black African, Black Caribbean and White British women in the UK. Design: In-depth qualitative interviews using grounded theory methods to identify themes. Findings validated through focus groups. Participants: 94 women aged 33–91 years; 20 Black African, 20 Black Caribbean and 20 White British women diagnosed with symptomatic breast cancer were interviewed. Fourteen Black African and 20 Black Caribbean women with (n=19) and without (n=15) breast cancer participated in six focus groups. Setting: Eight cancer centres/hospital trusts in London (n=5), Somerset (n=1), West Midlands (n=1) and Greater Manchester (n=1) during 2012–2013. Results: There are important differences and similarities in barriers to early diagnosis of breast cancer between Black African, Black Caribbean and White British women in the UK. Differences were influenced by country of birth, time spent in UK and age. First generation Black African women experienced most barriers and longest delays. Second generation Black Caribbean and White British women were similar and experienced fewest barriers. Absence of pain was a barrier for Black African and Black Caribbean women. Older White British women (≥70 years) and first generation Black African and Black Caribbean women shared conservative attitudes and taboos about breast awareness. All women viewed themselves at low risk of the disease, and voiced uncertainty over breast awareness and appraising non-lump symptoms. Focus group findings validated and expanded themes identified in interviews. Conclusions: Findings challenged reporting of Black women homogenously in breast cancer research. This can mask distinctions within and between ethnic groups. Current media and health promotion messages need reframing to promote early presentation with breast symptoms. Working with communities and developing culturally appropriate materials may lessen taboos and stigma, raise awareness, increase discussion of breast cancer and promote prompt help-seeking for breast symptoms among women with low cancer awareness.